The main reasons of growing need of the English language education - Жукова, Тетяна Василівна; Жукова, Татьяна Васильевна; Zhukova, Tetiana (My University, 2017)
UK: Деякі основні причини збільшення потреби у вивченні англійської мови обґрунтовуються у статті. Також представлені важливі переваги вивчення англійської мови у порівнянні з іншими мовами. EN: Some main reasons of growing need of the English language education in modern society are substantiated in the article. Significant advantages of learning English over other languages are presented.
Keywords: language education; language of communication; science; literature; information age; мовна освіта; мова спілкування; наука; література; інформаційний вік